Preference Modeling to Support Stakeholder Outreach toward the Common Fishery Policy Objectives in the North Mediterranean Sea - Lembo, Giuseppe; Bellido, Jose M.; Bitetto, Isabella; Facchini, Maria T.; García-Jiménez, Teresa; Stithou, Mavra; Vassilopoulou, Vassiliki C.; Spedicato, Maria T. (Frontiers in Marine Science, 2017)
Participatory management is a working method of paramount importance based on the principles of knowledge sharing and accountability for addressing the sustainable management of the fishery sector. To approach this multidimensional problem we applied two Multi Criteria Decision Analysis (MCDA) methods, the Analytic Hierarchy Process (AHP) and the Non-Structural Fuzzy Decision Support System (NSFDSS), which were applied incorporating uncertainty to generate probabilistic rankings. The NSFDSS technique was applied for the first time to address a fishery problem. Two surveys were carried out among Mediterranean Advisory Council (MEDAC) stakeholders with different backgrounds. By the two surveys we: i) made an AHP test for exploring stakeholders’ perception of the objectives and indicators used in the monitoring of the stocks, ecosystem, and fisheries, and ii) introduced the NSFDSS technique, gathering feedback on stakeholders’ preferences on management options for improving fishery sustainability (e.g., reducing discards, improving ecosystem state and economic yield in the long term). In the AHP the respondents were asked to evaluate the importance of one objective against another according to a scale of semantic scores from 1 to 5, whereas a simpler scoring scale, with only 3 possible options, was used in the NSFDSS. The two MCDA methods were proven to be useful to elicit stakeholders’ view on the potential effects of key issues on economic and environmental fishery sustainability. The results showed stakeholders’ awareness of the fact that the reproductive potential should be secured by checking mortality and/or fishing intensity. Consistently, among the ecological indicators that are tracking the fisheries policy objectives, a higher rank was attributed to “mean size of the spawners,” while cost efficiency was considered to be essential for improving profits. Regarding the economic indicators, stakeholders gave higher priority to “revenue” in comparison to “production (catches),” which is a sign of awareness that increasing fish production does not necessarily turn into increased revenue. Among the different management strategies, “fleet withdrawal” (scraping) was considered as the worst option, while the “combination of measures” was considered to be the best alternative for achieving a sustainable fishery in the long term.